Whistleblowing System Intention Internal Auditors in the Provincial Government of Dki Jakarta - Shafrullah, Faris; Indrawati, Leni; Ihsan, Faris; Ismail, Solahuddin; Supendi, Supendi; Akbar, Bahrullah; Effendy, Khasan; Lukman, Sampara; Kurniawati, Layla; Pratiwi, Putri Ayu (Journal of Posthumanism, 2025)
The study delves into the phenomenon of whistleblowing within the Jakarta Special Capital Region Government. Whistleblowers expose instances of corruption, financial anomalies and collusion by providing evidence through photos and videos, on social media platforms. This condition is exacerbated by the tendency on the part of the Government to not be serious about disclosing or on the part of the reporter there is a tendency to be afraid if there is a backlash against him. The aim of this research is to test the exogenous latent variables Perceived Organizational Support (POS), Capability (CAP), Attitude Toward Whistleblowing (ATW), Rationalization (RAS), Opportunity (OPP), Pressure (PRES), and the endogenous latent variable Whistleblowing System Intention (WBSI), and also the mediating variable is Perceived Behavioral Control (PBC). The method used was a sample of 450 employees working in the DKI Jakarta Provincial Government offices, and data processing was carried out using the Structural Equation Model. The test results for the Perceived Organizational Support, Capability, Attitude Toward Whistleblowing variables have a direct and significant positive influence on the Perceived Behavioral Control variable. The Whistleblowing System Intention variable is influenced directly and mediated by the Perceived Behavioral Control variable which is significantly positive, Rational is positively significant and Opportunity is positively significant. Meanwhile, the Pressure variable has a significant negative influence on the Perceived Behavioral Control variable and the Whistleblowing System Intention variable.